Environmental Factors and Genetic Diversity as Drivers of Early Gonadal Maturation: A Gonadosomatic Index Based Investigation on Indian Shad, Tenualosa ilisha Population of Bangladesh - Ahammad, A. K. Shakur; Hasan, Neaz A.; Haque, Mohammad Mahfujul; Bashar, Abul; Ahmed, Md. Borhan Uddin; Alam, Mohammad Ashraful; Asaduzzaman, Md.; Bashar, Md. Abul; Mahmud, Yahia (Frontiers in Marine Science, 2021)
In recent years, attaining gonadal maturation in smaller Hilsa (Tenualosa ilisha) has become a burning issue for Hilsa fishery of Bangladesh. Causes of early maturation are not yet clearly understood. Along with environmental parameters, genetic differentiation within the population was hypothesized as the main driver, and therefore, assessing the correlation between gonadosomatic index (GSI) and environmental factors and analyzing genetic diversity were set as objectives of the present study. To address these complex issues, six diverse habitats across Bangladesh were chosen for Hilsa sample collection. For GSI, gonad was dissected from fresh fish and preserved in Bouin’s fluid for histological observation. Water quality parameters such as temperature, dissolved oxygen, pH, and salinity were also assessed. 35 fish from each habitat were used to extract and amplify DNA through the PCR technique, and genetic diversity was examined. Further, to draw a firm conclusion, the phylogenetic tree of the Hilsa population was developed by the unweighted pair-group method of arithmetic mean method based on the Cyt b gene of mitochondrial DNA. Results of GSI studies revealed that peak spawning months of T. ilisha were in October and February, where October showed the highest values in all six habitats. Histological examination showed different stages of gonadal development in different sizes and ages of Hilsa. Among all sampling sites, no statistical difference was observed for GSI value; however, smaller sized and aged Hilsa being ripped were evident in Gaglajur Haor and Kali River. Among the observed water quality parameters, temperature correlated with GSI strongly. Increased GSI was observed with temperature augmentation from downstream to upper stream, irrespective of body size and age. A perplex correlation between dissolved oxygen of observed habitats and GSI was executed. Other physico-chemical parameters viz. pH and salinity exhibited weak and moderate positive association with the GSI, respectively. Haplotype diversity of mitochondrial DNA divided the Hilsa population into three possible sub-populations, where the most distant group (Gaglajur Haor and Kali River) was subjected to early gonadal maturity. Results of this study make clear conclusions regarding the role of environmental and genetic factors on early gonadal maturations, pointing fingers at the curse of climate change and anthropogenic stressors for the migration of the Hilsa fishery of Bangladesh.